Exploration of Road Safety Measures to Prevent Road Traffic Fatalities in South Africa - Mmakwena Modipa; Olutola Adewale; Kockott Sean (UIN Sunan Gunung Djati, 2022)
Road traffic accidents is a global problem where road users are losing their lives on the road even in South Africa is prevalent. Compliance to the rules of the road is important aspect of road safety and road users should play their part on the road. RTA is a collective responsibility and law enforcement agencies should lead this important task to ensure that road users are safe whenever they are on the road. The inability of law enforcement agencies to formulate road safety measures to address road traffic fatalities is a major problem in South Africa. This article focused on road safety measures to curb factors contributing to road traffic accidents in South Africa. The article is based on a qualitatively rooted methodology including a wide range of primary and secondary sources focusing on road safety measures to overcome road traffic accidents. The article further draws on the findings from the world on road safety measures and formulate steps to counteract road traffic accidents in South Africa. Road safety measures could play a critical role in changing the behaviour of road users other than just focusing on reducing road traffic accidents. The research based key steps leading to the prevention of road traffic accidents. The first step related to the process of raising awareness in road safety; capacitate law enforcement agencies with resources to address non-compliance on the road and lastly to strengthen partnerships in road safety to counteract road traffic fatalities.